2005
DOI: 10.3109/2000-1967-070
|View full text |Cite
|
Sign up to set email alerts
|

Pyogenic Liver Abscesses Secondary to Carcinoma of the Sigmoid Colon

Abstract: We report a case of liver abscesses associated with sigmoid colon cancer in an 81-yearold woman. The patient was referred to our hospital because of a tumorous lesion of the sigmoid colon. Five days before the scheduled operation, she presented abdominal pain, fever and chill. Imaging scans revealed multiple liver abscesses in both lobes, which were successfully treated with intravenously administered antibiotics. Two weeks later, the patient underwent laparoscopic-assisted sigmoidectomy. Nineteen cases of liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 5 publications
0
6
0
2
Order By: Relevance
“…Our data also showed 10-fold and 2-fold increases in the incidence and mortality rates of pyogenic liver abscess. In addition to the fact that tumors from the hepatobil- iary region might mimic abscesses (23)(24)(25), tumors in other regions were also associated with poor prognoses (26,27), confi rming malignancy itself as an independent aggravating factor. Because the prevalence of both renal disease and malignancy has increased in recent years, the threat of pyogenic liver abscess in those patients is becoming more important, worthy of our special notice.…”
Section: Discussionmentioning
confidence: 99%
“…Our data also showed 10-fold and 2-fold increases in the incidence and mortality rates of pyogenic liver abscess. In addition to the fact that tumors from the hepatobil- iary region might mimic abscesses (23)(24)(25), tumors in other regions were also associated with poor prognoses (26,27), confi rming malignancy itself as an independent aggravating factor. Because the prevalence of both renal disease and malignancy has increased in recent years, the threat of pyogenic liver abscess in those patients is becoming more important, worthy of our special notice.…”
Section: Discussionmentioning
confidence: 99%
“…There is an increasing association between colonic cancer and liver abscess over the last few years. It has been reported that a pyogenic liver abscess may be associated with, or be the initial presentation of an underlying rectosigmoid or colonic neoplasm [5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…In PLA not caused by Klebsiella (see below), the most common coexisting diseases are diabetes mellitus, followed by biliary stone disorders and other types of biliary tract disease (Rockey 2001), and intra-abdominal infectious and neoplastic disease (Lin et al 2011a;Law and Li 2012), in particular colonic disease (McDonald et al 1984), including colorectal cancer (Lonardo et al 1992;Yokota et al 2005;Pisano et al 2007. Silent colorectal cancer (CRC) can manifest as PLA in the absence of metastasis (Teitz et al 1995;Fernandez Ruiz et al 2007;Giuliani et al 2007;Hiraoka et al 2007;Chen et al 2012;Jeong et al 2012;Qu et al 2012), a constellation which is an important cancerinflammation syndrome (the CRC-PLA syndrome, as I tend to call it).…”
Section: Clinical Featuresmentioning
confidence: 99%